2015
DOI: 10.1007/s12161-015-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Vodka: A Review Paper

Abstract: Vodka is the most popular alcoholic beverage in Poland, Russia and other Eastern European countries, made from ethyl alcohol of agricultural origin that has been produced via fermentation of potatoes, grains or other agricultural products. Despite distillation and multiple filtering, it is not possible to produce 100 % ethanol. The solution with a minimum ethanol content of 96 %, which is used to produce vodkas, also contains trace amounts of other compounds such as, esters, aldehydes, higher alcohols, methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…At the beginning of the 21 st century, many distilleries began to experiment with the production of whiskey from rye, and several companies now produce high‐quality aged spirits . In Russia, vodka is produced, for the most part, from wheat, whereas in Poland rye is more frequently used as a raw material for this purpose . It was found that the increased dry‐matter content in rye‐based mashes could pose a problem in the achievement of higher fermentation efficiency, because of the large amounts of xylans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the 21 st century, many distilleries began to experiment with the production of whiskey from rye, and several companies now produce high‐quality aged spirits . In Russia, vodka is produced, for the most part, from wheat, whereas in Poland rye is more frequently used as a raw material for this purpose . It was found that the increased dry‐matter content in rye‐based mashes could pose a problem in the achievement of higher fermentation efficiency, because of the large amounts of xylans.…”
Section: Resultsmentioning
confidence: 99%
“…48,51 In Russia, vodka is produced, for the most part, from wheat, whereas in Poland rye is more frequently used as a raw material for this purpose. 52 It was found that the increased dry-matter content in rye-based mashes could pose a problem in the achievement of higher fermentation efficiency, because of the large amounts of xylans. Further research is therefore required to improve this universal method of spirit production.…”
Section: Fermentation Indicatorsmentioning
confidence: 99%
“…If the aversive properties of ethanol, particularly bitterness, were important in mediating alcohol intake, it would be expected to be most obvious in the unmixed spirits category, as these products are most similar to simple aqueous ethanol solutions (Wisniewska et al, 2015).…”
Section: Bitterness and Sournessmentioning
confidence: 99%
“…Onuki et al (28) developed SPME-based quantification for 10 major fermentation by-products in industrial ethanol. A comprehensive review of vodka analyses methods was published by Wiśniewska et al (97) as well as a comprehensive review of applications of gas chromatography to the analysis of spirit-based alcoholic beverages (98). A comprehensive review of vodka analyses methods was published by Wiśniewska et al (97) as well as a comprehensive review of applications of gas chromatography to the analysis of spirit-based alcoholic beverages (98).…”
Section: Techniques Used For Ethanol Analysismentioning
confidence: 99%